Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element using the same

By introducing polymers with specific structures into the liquid crystal alignment agent, the problems of insufficient liquid crystal orientation stability and electrostatic accumulation of liquid crystal display elements in the transverse electric field are solved, and higher display contrast and lower scintillation rate are achieved.

CN114651207BActive Publication Date: 2025-03-18NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080077623.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-14
Filing Date
2020-11-02
Publication Date
2025-03-18
Estimated Expiration
2040-11-02

AI Technical Summary

Technical Problem

In the lateral electric field mode, the stability of the liquid crystal orientation of the existing liquid crystal display elements is insufficient, resulting in lower display contrast, afterimage and flickering problems, and static electricity is easily accumulated, affecting the display quality.

Method used

By introducing a polyimide precursor of a specific structure and its imidized polymer into the polymer in the liquid crystal alignment agent, the stability of the liquid crystal orientation is improved and charge accumulation is reduced.

Benefits of technology

It achieves excellent stability of liquid crystal orientation, reduces the occurrence of flicker during driving, improves display contrast and quality, and reduces the impact of static accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114651207B_ABST
    Figure CN114651207B_ABST
Patent Text Reader

Abstract

The present invention provides a liquid crystal alignment agent that can obtain a liquid crystal alignment film with excellent stability of liquid crystal orientation and less prone to flickering during driving. The liquid crystal alignment agent of the present invention is characterized in that it contains at least one polymer (A) selected from the group consisting of a polyimide precursor (a1) having a repeating unit represented by the following formula (1), and an imidized polymer (a2) of the polyimide precursor (a1), wherein the polyimide precursor (a1) contains a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-1), and a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-2). (In formula (1), X1 is a tetravalent organic group, Y1 is a divalent organic group, R1, R2, A1, and A2 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In the molecular chain of the polyimide precursor (a1), X1, R1, R2, A1, and A2 are each optionally present as one or as a mixture of two or more. Y1 is optionally present as a mixture of two or more.) (In formula (Y1-1) and formula (Y1-2), Z1, Z2, Z3, and Z4 are each independently a halogen atom or an alkyl group having 1 to 4 carbon atoms, and n is an integer of 0 to 4. n is optionally the same or different. When n is an integer greater than 2, Z1, Z2, Z3, and Z4 are each optionally the same or different.)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element including the liquid crystal aligning film using the liquid crystal aligning agent. Background Art

[0002] Liquid crystal display elements are widely used as display parts of personal computers, mobile phones, smart phones, televisions, etc. Liquid crystal devices, for example, include: a liquid crystal layer, which is sandwiched between an element substrate and a color filter substrate; pixel electrodes and common electrodes, which apply an electric field to the liquid crystal layer; an orientation film, which controls the orientation of liquid crystal molecules in the liquid crystal layer; and a thin film transistor (TFT: Thin Film Transistor), which switches the electrical signal supplied to the pixel electrode, etc. As a driving method for liquid crystal molecules, longitudinal electric field methods such as TN (Twisted Nematic) method and VA (Vertical Alignment: Vertical Alignment) method are known; transverse electric field methods such as IPS (In-Plane Switching: Plane Switching) method and FFS (Fringe Field Switching: Fringe Field Switching) method are known. In the transverse electric field method in which electrodes are formed only on one side of the substrate and an electric field is applied in a direction parallel to the substrate, compared with the existing longitudinal electric field method in which voltage is applied to electrodes formed on the upper and lower substrates to drive the liquid crystal, a liquid crystal display element having a wide viewing angle characteristic and capable of high-quality display is known.

[0003] Although the liquid crystal box (cell) of the transverse electric field method has excellent viewing angle characteristics, the electrode portion formed in the substrate is small. Therefore, when the voltage holding rate is low, it is impossible to apply sufficient voltage to the liquid crystal, and the display contrast is reduced. In addition, if the stability of the liquid crystal orientation is small, the liquid crystal cannot return to its original state when it is driven for a long time, which becomes the cause of reduced contrast and afterimages. Therefore, the stability of the liquid crystal orientation is important. In addition, static electricity is easily accumulated in the liquid crystal box. Due to the application of positive and negative asymmetric voltages generated by driving, charges accumulate in the liquid crystal box. These accumulated charges affect the display as a disorder of the liquid crystal orientation and afterimages, significantly reducing the display quality level of the liquid crystal element. In addition, because the backlight irradiates the liquid crystal box just after driving, the charges accumulate, which causes the following problems: afterimages are generated even for a short time, or the size of flickers (flicker) changes during driving.

[0004] As a liquid crystal aligning agent that has excellent voltage retention and reduces charge accumulation when using such a liquid crystal display element of a transverse electric field mode, a liquid crystal aligning agent containing a polymer obtained by polycondensing a specific diamine and an aliphatic tetracarboxylic acid derivative is disclosed in Patent Document 1. However, as the performance of liquid crystal display elements increases, the properties required for liquid crystal alignment films also become more stringent, and these prior arts are difficult to fully meet all the required properties.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. WO2004 / 021076 Pamphlet Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present invention aims to provide a liquid crystal alignment agent that can obtain a liquid crystal alignment film that has excellent stability in liquid crystal alignment and is less likely to flicker during driving, a liquid crystal alignment film obtained from the liquid crystal alignment agent, and a liquid crystal display element using the liquid crystal alignment film.

[0010] Solutions for solving problems

[0011] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be improved by introducing a plurality of specific structures into a polymer contained in a liquid crystal aligning agent, thereby completing the present invention.

[0012] The present invention has been completed based on these findings, and has the following contents as its main gist.

[0013] A liquid crystal alignment agent, characterized in that it contains at least one polymer (A) selected from the group consisting of a polyimide precursor (a1) having a repeating unit represented by the following formula (1), and an imidized polymer (a2) of the polyimide precursor (a1), wherein the polyimide precursor (a1) includes a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-1), and a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-2).

[0014]

[0015] (In formula (1), X1 is a tetravalent organic group, Y1 is a divalent organic group, R1, R2, A1, and A2 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In the molecular chain of the polyimide precursor (a1), X1, R1, R2, A1, and A2 are each optionally present as one or as a mixture of two or more. Y1 is optionally present as a mixture of two or more.)

[0016]

[0017] (In formula (Y1-1) and formula (Y1-2), Z1, Z2, Z3 and Z4 are each independently a halogen atom or an alkyl group having 1 to 4 carbon atoms, and n is an integer of 0 to 4. n may be the same or different. When n is an integer of 2 or more, Z1, Z2, Z3 and Z4 may be the same or different.)

[0018] Effects of the Invention

[0019] According to the liquid crystal aligning agent of the present invention, it is possible to obtain a liquid crystal aligning film which is excellent in the stability of liquid crystal alignment and hardly causes flickering during driving. DETAILED DESCRIPTION

[0020] The liquid crystal aligning agent of this invention contains the polymer (A) mentioned below.

[0021] <Polymer (A)>

[0022] The polymer (A) used in the present invention is at least one polymer selected from the group consisting of a polyimide precursor (a1) containing a repeating unit represented by the above formula (1) and an imidized polymer (a2) of the polyimide precursor (a1).

[0023] In the formula (1), Y1 is a divalent organic group. The polyimide precursor (a1) includes a structure in which Y1 in the formula (1) is a divalent group represented by the formula (Y1-1) and a structure in which Y1 in the formula (1) is a divalent group represented by the formula (Y1-2).

[0024] In the formula (Y1-1) and the formula (Y1-2), Z1, Z2, Z3 and Z4 are preferably each independently a fluorine atom or a methyl group, and n is preferably an integer of 0-1.

[0025] It is preferred that the divalent group represented by the formula (Y1-1) is at least one selected from the group consisting of structures represented by the following formulae (D2-1) to (D2-5).

[0026]

[0027] (In formulas (D2-1) to (D2-5), * represents a bonding bond.)

[0028] It is preferred that the divalent group represented by the formula (Y1-2) is at least one selected from the group consisting of structures represented by the following formulae (D4-1) to (D4-5).

[0029]

[0030] (In formulas (D4-1) to (D4-5), * represents a bonding bond.)

[0031] In the polyimide precursor (a1), the proportion of the divalent group represented by Y1 as the formula (Y1-1) and the proportion of the divalent group represented by Y1 as the formula (Y1-2) are not particularly limited. Relative to the overall structure of the formula (1) possessed by the polyimide precursor (a1), the proportion of Y1 as the formula (Y1-1) is preferably 10 to 50 mol%, more preferably 20 to 40 mol%, and the proportion of Y1 as the formula (Y1-2) is preferably 10 to 50 mol%, more preferably 20 to 40 mol%.

[0032] The total of the ratio of Y1 being the formula (Y1-1) and the ratio of Y1 being the formula (Y1-2) is preferably 20 to 80 mol %, more preferably 40 to 60 mol %.

[0033] The molecular chain of the polyimide precursor (a1) may further include a structure in which Y1 in the formula (1) is a divalent organic group other than the formula (Y1-1) and the formula (Y1-2). In addition, the structure of Y1 as a group other than the formula (Y1-1) and the formula (Y1-2) may optionally exist in one type or in a mixture of two or more types in the molecular chain of the polyimide precursor (a1).

[0034] Preferred specific examples of Y1 other than Formula (Y1-1) and Formula (Y1-2) are listed below, but the present invention is not limited thereto.

[0035]

[0036] Furthermore, Y1 may be a structure of any of the following groups.

[0037]

[0038] The above-mentioned Boc represents a group shown below.

[0039]

[0040] The total ratio of Y1 representing the above-mentioned formula (Y1-3) to (Y1-10) and formula (5-1) to (5-9) is preferably 10 to 80 mol %, more preferably 20 to 60 mol %, and even more preferably 40 to 60 mol % based on the entire structure of formula (1) possessed by the polyimide precursor (a1).

[0041] In the polyimide precursor (a1), X1 is a tetravalent organic group.

[0042] Although preferred structures of X1 in the polyimide precursor (a1) are shown below, the present invention is not limited thereto.

[0043]

[0044] In the polyimide precursor (a1), R1, R2, A1, and A2 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Preferably, R1, R2, A1, and A2 are each independently a hydrogen atom or a methyl group.

[0045] The polyimide precursor (a1) used in the present invention can be obtained by polycondensation of a tetracarboxylic acid derivative component including a tetracarboxylic acid derivative as a source of X1 of the formula (1) and a diamine component including a diamine as a source of Y1 of the formula (1).

[0046] As an example of a polyimide precursor, a polyamic acid, a polyamic acid ester, etc. are mentioned.

[0047] As an example of a tetracarboxylic acid derivative, tetracarboxylic dianhydride, tetracarboxylic acid disilyl ester, tetracarboxylic acid dichloride, tetracarboxylic acid dialkyl ester, tetracarboxylic acid diene ester, tetracarboxylic acid dialkyl ester dichloride etc. are mentioned.

[0048] In addition, the polyimide precursor (a1) may also be a polymer with a modified or blocked main chain end. The polyimide precursor (a1) with a modified or blocked main chain end may be obtained by reacting a monofunctional compound with a tetracarboxylic acid derivative component and / or a diamine component during or after the polycondensation reaction of the tetracarboxylic acid derivative component and the diamine component. Examples of the monofunctional compound include monoamines, monoisocyanates, compounds having an acid anhydride group, compounds having an acid chloride group, and the like.

[0049] The reaction conditions and the like for synthesizing the polyimide precursor (a1) using the tetracarboxylic acid derivative component and the diamine component are not particularly limited, and a known method can be used.

[0050] The imidized polymer (a2) used in the polymer (A) of the present invention is a polymer having a structure in which A1-OR1 and / or A2-OR2 are separated from the polyimide precursor (a1) and ring-closed (also referred to as imidization). The ring-closure ratio (also referred to as imidization ratio) in this case can be arbitrarily selected as needed.

[0051] It should be noted that in this specification, the imidization rate refers to the ratio of the imide group to the total amount of the imide group and the carboxyl group (or its derivative) derived from tetracarboxylic dianhydride or its derivative. In the imidized polymer, the imidization rate does not necessarily need to be 100%, and can be adjusted arbitrarily according to the use and purpose. The imidization rate of the imidized polymer used in the present invention is preferably 20 to 100%, and more preferably 50 to 99%.

[0052] The imidized polymer (a2) can be synthesized by imidizing the polyimide precursor (a1) by a known method, or by using a raw material having an imidized structure of formula (1) (for example, an imide group-containing diamine compound described in Japanese Patent Application Laid-Open No. 9-185064).

[0053] The molecular weight of the polymer (A) in the present invention is not particularly limited as long as a good coating film can be formed. For example, the weight average molecular weight is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000. In addition, the number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.

[0054] <Liquid crystal alignment agent>

[0055] The liquid crystal aligning agent of the present invention may contain polymers other than polymer (A) in addition to polymer (A). The types of polymers other than polymer (A) are not particularly limited, and examples thereof include polyamic acid, polyamic acid ester, polyimide, polysiloxane, polyester, cellulose derivative, polyacetal, polystyrene derivative, poly(styrene-maleimide) derivative, poly(meth)acrylate, etc. Among polymers other than polymer (A), the polymer (B) shown below is preferably a component contained in the liquid crystal aligning agent of the present invention.

[0056] Polymer (B): at least one polymer selected from the group consisting of a polyimide precursor (b1) having a repeating unit represented by the following formula (2), and an imidized polymer (b2) of the polyimide precursor (b1), wherein the polyimide precursor (b1) contains a structure in which Y2 in the following formula (2) is a divalent organic group having (i) a nitrogen atom bonded to an aromatic group or (ii) a nitrogen-containing aromatic heterocycle.

[0057]

[0058] (In formula (2), X2 is a tetravalent organic group, Y2 is a divalent organic group, and A3 and A4 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In the molecular chain of the polyimide precursor (b1), X2, Y2, A3 and A4 are each optionally present as one or as a mixture of two or more.)

[0059] The polymer (B) is preferably at least one polymer selected from the polyimide precursor (b1).

[0060] Particularly preferred examples are shown below as the structure of Y2 having (i) a nitrogen atom bonded to an aromatic group or (ii) a nitrogen-containing aromatic heterocyclic ring.

[0061]

[0062]

[0063] The polymer (B) may also contain a structure in which Y2 is a divalent organic group other than the above. Examples of divalent organic groups other than the above include: the specific structure of Y1 exemplified in the polymer (A); a structure in which two amino groups are removed from a diamine having a carboxyl group, such as 2,5-diaminobenzoic acid and 3,5-diaminobenzoic acid; a structure in which two amino groups are removed from a diamine having a urea bond, such as 1,3-bis(4-aminophenethyl)urea, 1,3-bis(4-aminobenzyl)urea, 1,3-bis(3-aminobenzyl)urea, 1-(4-aminobenzyl)-3-(4-aminophenethyl)urea, but are not limited thereto.

[0064] Preferred examples of the structure of X2 include the specific structures of X1 exemplified in the polymer (A) and the tetravalent groups described below.

[0065]

[0066] The molecular weight of the polymer (B) is not particularly limited as long as a good coating film can be formed, and for example, the weight average molecular weight is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000. The number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.

[0067] When the polymer (A) and the polymer (B) are contained in the liquid crystal aligning agent of the present invention, it is preferable that content of the polymer (B) is 20-80 mass % with respect to the total of the polymer (A) and the polymer (B).

[0068] The liquid crystal aligning agent of the present invention may also contain components other than polymers. As components other than polymers, there can be listed: dielectrics or conductive substances for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal aligning film; silane coupling agents for the purpose of improving the adhesion between the liquid crystal aligning film and the substrate; crosslinking compounds for the purpose of improving the hardness and density of the film when used as a liquid crystal aligning film; and imidization accelerators for the purpose of efficiently performing imidization of polyamic acid when the coating film is fired.

[0069] The liquid crystal aligning agent of the present invention is a substance for making a liquid crystal aligning film. From the viewpoint of forming a uniform film, it is preferred to dissolve the above-mentioned components in an organic solvent to form a coating liquid. The concentration of the coating liquid is appropriately changed according to the coating device used and the thickness of the liquid crystal aligning film to be obtained. From the perspective of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the perspective of the storage stability of the solution, it is preferably set to 10% by mass or less. The concentration of the particularly preferred polymer is 2 to 8% by mass.

[0070] Although content of the polymer (A) in the liquid crystal aligning agent can be appropriately changed according to the coating method of the liquid crystal aligning agent and the film thickness of the target liquid crystal aligning film, it is preferably 2 to 10 mass %, particularly preferably 3 to 7 mass %.

[0071] The organic solvent used in the above-mentioned coating solution is not particularly limited as long as it dissolves the polymer component uniformly. If specific examples are listed, they include: N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone is preferably used. These solvents can also be used in combination of two or more.

[0072] In addition, in the composition for the purpose of film formation, in addition to the solvent as described above, a mixed solvent is usually used to add a solvent that improves the coating property and the smoothness of the film surface. In the liquid crystal aligning agent of the present invention, such a mixed solvent is also preferably used. Specific examples of the organic solvent to be mixed are listed below, but are not limited to these examples.

[0073] For example, ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1 , 3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, 1,4-dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate , ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, Diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, and solvents represented by the following formulas [D-1] to [D-3].

[0074]

[0075] (R in formula [D-1] and formula [D-2] represents an alkyl group having 1 to 3 carbon atoms, and R in formula [D-3] represents an alkyl group having 1 to 4 carbon atoms.)

[0076] Among the above, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether or dipropylene glycol dimethyl ether are preferred. The type and content of such solvents are appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent. In addition, these solvents can also be used in combination of two or more.

[0077] <Liquid crystal alignment film>

[0078] The liquid crystal alignment film of the present invention is obtained from the liquid crystal alignment agent of the present invention. If an example of a method for obtaining a liquid crystal alignment film from a liquid crystal alignment agent is given, the following method can be given: the liquid crystal alignment agent in the form of a coating liquid is applied to a substrate, and the film obtained by drying and firing is subjected to an alignment treatment by a brushing treatment method or a photo-alignment treatment method.

[0079] The substrate on which the liquid crystal alignment agent is applied is not particularly limited, and may also be a glass substrate, a silicon nitride substrate, an acrylic substrate, a plastic substrate such as a polycarbonate substrate, etc. In this case, if a substrate having an ITO electrode or the like for driving the liquid crystal is used, it is preferred from the perspective of simplifying the process. In addition, in a reflective liquid crystal display element, if only a single-sided substrate is used, an opaque object such as a silicon wafer may also be used, and in this case, the electrode may also be made of a light-reflecting material such as aluminum.

[0080] The coating method of the liquid crystal aligning agent is not particularly limited, and is generally industrially screen printing, offset printing, flexographic printing, inkjet printing, etc. Other coating methods include dipping, roll coating, slit coating, spin coating, spray coating, etc., and these can be used according to the purpose.

[0081] After the liquid crystal alignment agent is applied to the substrate, the solvent is evaporated and fired by a heating unit such as a heating plate, a heat circulation oven, an IR (infrared) oven, etc. The drying and firing steps after the liquid crystal alignment agent is applied can select any temperature and time. Usually, in order to fully remove the contained solvent, the conditions of firing at 50 to 120°C for 1 to 10 minutes and then firing at 150 to 300°C for 5 to 120 minutes can be listed.

[0082] Although the thickness of the liquid crystal aligning film after baking is not particularly limited, if it is too thin, the reliability of the liquid crystal display element may decrease, so it is preferably 5 to 300 nm, more preferably 10 to 200 nm.

[0083] The liquid crystal aligning film of the present invention is preferably used as a liquid crystal aligning film for a liquid crystal display element of a transverse electric field system such as an IPS system or an FFS system, and is particularly useful as a liquid crystal aligning film for a liquid crystal display element of an FFS system.

[0084] <Liquid crystal display device>

[0085] The liquid crystal display element of the present invention is prepared by obtaining a substrate having a liquid crystal alignment film obtained from the above-mentioned liquid crystal alignment agent, and then preparing a liquid crystal cell by a known method, and using the liquid crystal cell as an element.

[0086] An example of a method for manufacturing a liquid crystal cell is listed below, but the present invention is not limited thereto.

[0087] First, a set of substrates having electrodes for driving liquid crystals are prepared. The electrodes may be, for example, ITO electrodes, which are patterned in a manner that enables the desired image display. In addition, conversion elements such as TFTs (Thin Film Transistors) may be provided in each pixel portion constituting the image display. A liquid crystal alignment film is formed on the substrate as described above.

[0088] Next, a UV-curable sealant is arranged at a specified location on one of the two substrates on which a liquid crystal alignment film is formed, for example, and liquid crystals are arranged at several specified locations on the surface of the liquid crystal alignment film. The other substrate is then bonded and crimped in a manner that the liquid crystal alignment film is opposed to the other substrate, and the liquid crystal is pressed and spread to the front surface of the liquid crystal alignment film. Ultraviolet rays are then irradiated onto the entire surface of the substrate to cure the sealant, thereby obtaining a liquid crystal box.

[0089] Alternatively, as a process after forming a liquid crystal alignment film on a substrate, when a sealant is arranged at a predetermined location on one substrate, an opening that can be filled with liquid crystal from the outside is pre-set, and after the substrates are bonded without arranging liquid crystal, a liquid crystal material is injected into the liquid crystal box through the opening provided in the sealant, and then the opening is sealed with an adhesive to obtain a liquid crystal box. The injection of the liquid crystal material may be a vacuum injection method or a method utilizing a capillary phenomenon in the atmosphere.

[0090] In any of the above methods, in order to ensure a space for the liquid crystal material to be filled in the liquid crystal cell, it is preferred to provide columnar protrusions on one substrate, scatter spacers on one substrate, mix spacers into the sealant, or combine these methods.

[0091] As the above-mentioned liquid crystal material, there can be listed: nematic liquid crystal and smectic liquid crystal, etc., among which nematic liquid crystal is preferred, and any of positive liquid crystal material and negative liquid crystal material can also be used. Next, a polarizing plate is set. Specifically, it is preferred to attach a pair of polarizing plates to the surface of the two substrates on the opposite side of the liquid crystal layer.

[0092] Example

[0093] The present invention will be specifically described below with reference to Examples, etc., but the present invention is not limited to these Examples. The abbreviations of compounds and solvents and the methods for evaluating properties are as follows.

[0094] NMP: N-methyl-2-pyrrolidone.

[0095] BCS: Butyl Cellosolve.

[0096] DA-1 to DA-10: compounds of the following structural formulas.

[0097] CA-1 to CA-3: compounds of the following structural formulas.

[0098] AD-1 and AD-2: compounds of the following structural formulas.

[0099]

[0100] [Viscosity measurement]

[0101] In the following synthesis examples, the viscosity of the polymer solution was measured at 25° C. using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample volume of 1.1 mL and a conical rotor TE-1 (1°34′, R24).

[0102] <Polymer Synthesis>

[0103] (Synthesis example 1)

[0104] DA-1 (1.980 g, 8.1 mmol), DA-2 (1.471 g, 5.4 mmol), DA-3 (0.876 g, 8.1 mmol), and DA-4 (2.152 g, 5.4 mmol) were added to a 200 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (65.49 g) was added and stirred to dissolve while nitrogen was supplied. CA-1 (5.750 g, 25.7 mmol) and NMP (24.17 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain an NMP solution of polyamic acid (PAA-A1). The viscosity of the polyamic acid solution was 378 mPa·s.

[0105] (Synthesis example 2)

[0106] DA-1 (2.052 g, 8.4 mmol), DA-2 (1.525 g, 5.6 mmol), DA-3 (0.908 g, 8.4 mmol), and DA-5 (1.912 g, 5.6 mmol) were added to a 200 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (65.23 g) was added and stirred to dissolve while nitrogen was supplied. CA-1 (6.026 g, 26.9 mmol) and NMP (25.90 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain an NMP solution of polyamic acid (PAA-A2). The viscosity of the polyamic acid solution was 408 mPa·s.

[0107] (Synthesis example 3)

[0108] DA-7 (19.925 g, 100.0 mmol) and DA-9 (7.460 g, 25.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (365.63 g) was added and stirred to dissolve while nitrogen was supplied. CA-3 (34.939 g, 118.8 mmol) and NMP (91.41 g) were added while stirring the solution, and then stirred at 50°C for 12 hours to obtain an NMP solution of polyamic acid (PAA-B1). The viscosity of the polyamic acid solution was 398 mPa·s.

[0109] (Synthesis Example 4)

[0110] DA-7 (19.925 g, 100.0 mmol) and DA-9 (7.460 g, 25.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (359.54 g) was added and stirred to dissolve while nitrogen was supplied. CA-2 (22.552 g, 115.0 mmol) and NMP (89.89 g) were added while stirring the solution, and then stirred at 50° C. for 12 hours to obtain an NMP solution of polyamic acid (PAA-B2). The viscosity of the polyamic acid solution was 135 mPa·s.

[0111] (Synthesis Example 5)

[0112] DA-7 (9.963 g, 50.0 mmol), DA-8 (10.664 g, 50.0 mmol), and DA-9 (7.460 g, 25.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (366.36 g) was added and stirred to dissolve while nitrogen was supplied. CA-2 (22.797 g, 116.2 mmol) and NMP (91.59 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain an NMP solution of polyamic acid (PAA-B3). The viscosity of the polyamic acid solution was 91 mPa·s.

[0113] (Comparative Synthesis Example 1)

[0114] DA-1 (9.161 g, 37.5 mmol), DA-6 (12.014 g, 37.5 mmol), DA-3 (2.704 g, 25.0 mmol), and DA-4 (9.963 g, 25.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (310.37 g) was added and stirred to dissolve while nitrogen was supplied. CA-1 (26.620 g, 118.7 mmol) and NMP (133.02 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain a solution of polyamic acid (PAA-C1). The viscosity of the polyamic acid solution was 405 mPa·s.

[0115] (Comparative Synthesis Example 2)

[0116] DA-1 (5.863 g, 24.0 mmol), DA-6 (7.689 g, 24.0 mmol), DA-3 (1.730 g, 16.0 mmol), and DA-5 (5.463 g, 16.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (194.41 g) was added and stirred to dissolve while nitrogen was supplied. CA-1 (17.127 g, 76.4 mmol) and NMP (83.32 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain a solution of polyamic acid (PAA-C2). The viscosity of the polyamic acid solution was 426 mPa·s.

[0117] (Comparative Synthesis Example 3)

[0118] DA-1 (9.161 g, 37.5 mmol), DA-10 (6.458 g, 25.0 mmol), DA-3 (4.055 g, 37.5 mmol), and DA-4 (9.963 g, 25.0 mmol) were added to a 1000 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and then NMP (288.79 g) was added and stirred to dissolve while nitrogen was supplied. CA-1 (26.620, 118.8 mmol) and NMP (123.77 g) were added while stirring the solution, and the mixture was further stirred at 50° C. for 12 hours to obtain a solution of polyamic acid (PAA-C3). The viscosity of the polyamic acid solution was 399 mPa·s.

[0119] (Examples and Comparative Examples)

[0120] The polymer solutions obtained in Synthesis Examples 1 to 5 and Comparative Synthesis Examples 1 to 3, AD-1, AD-2, NMP, and BCS were mixed and stirred at room temperature for 2 hours to obtain liquid crystal aligning agents of compositions shown in Table 1 below (the numbers in parentheses represent mass %).

[0121] [Table 1]

[0122]

[0123] An FFS drive liquid crystal cell was produced in the following manner using the liquid crystal aligning agent obtained above, and the characteristics were evaluated.

[0124] [Configuration of FFS drive liquid crystal cell]

[0125] In the case of a liquid crystal box for a fringe field switching (FFS) mode, a first glass substrate and a second glass substrate are set as a group, wherein the first glass substrate has a FOP (Finger on Plate) electrode layer formed of a common electrode in a planar shape, an insulating layer, and a pixel electrode in a comb-tooth shape on the surface, and the second glass substrate has a columnar spacer with a height of 3.5 μm on the surface, and an ITO film for anti-static is formed on the back. The above-mentioned pixel electrode has a comb-tooth shape, and the comb-tooth shape is a shape in which a plurality of electrode elements with a width of 3 μm bent at an inner angle of 160° in the central part are arranged in parallel at intervals of 6 μm, and a pixel has a first area and a second area with a line connecting the bent parts of the plurality of electrode elements as a boundary.

[0126] It should be noted that the liquid crystal orientation film formed on the first glass substrate is oriented in a manner such that the direction dividing the inner angle of the pixel bending portion into equal parts is orthogonal to the orientation direction of the liquid crystal, and the liquid crystal orientation film formed on the second glass substrate is oriented in a manner such that the orientation direction of the liquid crystal on the first substrate is consistent with the orientation direction of the liquid crystal on the second substrate when manufacturing the liquid crystal unit.

[0127] [Production of Liquid Crystal Cell]

[0128] After filtering the liquid crystal alignment agent with a filter having a pore size of 1.0 μm, the liquid crystal alignment agent was spin-coated on the above-mentioned substrate with electrodes and the counter substrate. Then, the liquid crystal alignment agent was dried on a hot plate at 80°C for 2 minutes and then fired at 230°C for 30 minutes to form a coating film with a thickness of 100 nm. A polyimide film was obtained on each substrate. The coating film surface was irradiated with 200 mJ / cm 2 Ultraviolet rays with a wavelength of 254 nm and linear polarization having an extinction ratio of 26: 1 were emitted. The substrate was fired at 230° C. for 30 minutes to obtain a substrate with a liquid crystal alignment film.

[0129] Next, a sealant was printed on one side of the above-mentioned set of substrates with a liquid crystal alignment film, and the other substrate was bonded in such a way that the liquid crystal alignment film faces each other, and the sealant was cured to produce an empty box. Liquid crystal (MLC-3019 manufactured by MERCK) was vacuum injected into the empty box at room temperature by a reduced pressure injection method, and the injection port was sealed to obtain an FFS-driven liquid crystal box. Then, the obtained liquid crystal box was heated at 120°C for 1 hour, left overnight, and used for each evaluation.

[0130] <Evaluation of Liquid Crystal Orientation Stability>

[0131] The prepared FFS drive liquid crystal cell was subjected to an AC voltage of ±5 V at a frequency of 60 Hz for 120 hours at a constant temperature of 60° C. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at room temperature for one day.

[0132] Regarding the liquid crystal cell subjected to the above-described processing, the deviation between the alignment direction of the liquid crystal in the first region of the pixel and the alignment direction of the liquid crystal in the second region in the state where no voltage is applied is calculated as an angle.

[0133] Specifically, a liquid crystal box is set between two polarizing plates arranged in a manner such that the polarization axes are orthogonal, the backlight is turned on, and the configuration angle of the liquid crystal box is adjusted in such a way that the transmitted light intensity of the first area of ​​the pixel is minimized. Then, the rotation angle required to rotate the liquid crystal box in such a way that the transmitted light intensity of the second area of ​​the pixel is minimized is calculated.

[0134] It can be said that the smaller the value of the rotation angle is, the better the stability of the liquid crystal orientation is. When the value of the rotation angle is 0.1° or less, it is evaluated as "good", and when it exceeds 0.1°, it is evaluated as "bad".

[0135] <Evaluation of flickering during driving>

[0136] The above-made liquid crystal box was set between two polarizing plates arranged in a manner that the polarization axes were orthogonal. The LED backlight was lit without voltage being applied, and the configuration angle of the liquid crystal box was adjusted so that the brightness of the transmitted light was minimized. Then, while applying an AC voltage with a frequency of 30 Hz to the liquid crystal box, the V-T curve (voltage-transmittance curve) was measured, and the AC voltage at which the relative transmittance became 23% was calculated as the driving voltage.

[0137] In the flicker measurement, the pre-lit LED backlight was temporarily turned off, and after being placed in a light-shielded state for 72 hours, the LED backlight was turned on again. At the same time as the backlight was turned on, an AC voltage with a relative transmittance of 23% and a frequency of 30Hz was applied, and the liquid crystal box was driven for 60 minutes to track the flicker amplitude. As for the flicker amplitude, the data collection / data recorder switch unit 34970A (made by Agilent technologies) connected via a photodiode and an I-V conversion amplifier was used to read the transmitted light of the LED backlight that passed through the two polarizing plates and the liquid crystal box between them. Based on this data, the value calculated using the following formula is used as the flicker level.

[0138] Flicker level (%) = {flicker amplitude / (2×z)}×100

[0139] In the above formula, z is the value obtained by reading the brightness when driven with an AC voltage of 30 Hz and a relative transmittance of 23% using the data collection / data recorder switch unit 34970A.

[0140] The flicker evaluation was performed by defining a "○" when the flicker level was maintained below 3.0% from the time the LED backlight was turned on and the AC voltage was applied until 60 minutes had passed. The flicker level was defined as "×" when it exceeded 3.0% within 60 minutes.

[0141] The evaluation of the flicker level according to the above method was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.

[0142] <Evaluation Results>

[0143] Table 2 shows the evaluation results of the stability of the liquid crystal alignment and the flicker generated during driving, which were performed on the liquid crystal display elements using the liquid crystal aligning agents of the above-mentioned Examples and Comparative Examples.

[0144] [Table 2]

[0145]

[0146] According to Examples 1 to 5, a liquid crystal alignment film having excellent stability in liquid crystal alignment and in which flickering is unlikely to occur can be obtained.

[0147] On the other hand, the stability of the liquid crystal orientation of the liquid crystal aligning films obtained in Comparative Examples 1 to 3 was “good”, but the flicker level was “×”.

[0148] Industrial Applicability

[0149] The liquid crystal alignment agent of the present invention is widely used in: TN mode, VA mode and other longitudinal electric field mode liquid crystal display elements; IPS mode, FFS mode and other transverse electric field mode liquid crystal display elements, especially widely used in IPS mode, FFS mode and other transverse electric field mode liquid crystal display elements.

[0150] It should be noted that the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2019-206332 filed on November 14, 2019 are incorporated herein by reference and introduced as a disclosure of the specification of the present invention.

Claims

1. A liquid crystal alignment agent, characterized in that: A polymer (A) containing at least one selected from the group consisting of a polyimide precursor (a1) having a repeating unit represented by the following formula (1) and an imidized polymer (a2) of the polyimide precursor (a1), The polyimide precursor (a1) includes a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-1), and a structure in which Y1 in the following formula (1) is a divalent group represented by the following formula (Y1-2). In formula (1), X1 is a tetravalent organic group, Y1 is a divalent organic group, R1, R2, A1, and A2 are independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; in the molecular chain of the polyimide precursor (a1), X1, R1, R2, A1, and A2 are each optionally present as one or a mixture of two or more; Y1 is optionally present as a mixture of two or more, In formula (Y1-1) and formula (Y1-2), Z1, Z2, Z3 and Z4 are each independently a halogen atom or an alkyl group having 1 to 4 carbon atoms, and n is an integer of 0 to 4; n is optionally the same or different; when n is an integer of 2 or more, Z1, Z2, Z3 and Z4 are each optionally the same or different, The divalent group represented by the formula (Y1-1) is at least one selected from the group consisting of structures represented by the following formulae (D2-1) to (D2-5), In formulas (D2-1) to (D2-5), * represents a bonding bond, The divalent group represented by the formula (Y1-2) is at least one selected from the group consisting of structures represented by the following formulae (D4-1) to (D4-5), In formulae (D4-1) to (D4-5), * represents a bonding bond.

2. The liquid crystal alignment agent according to claim 1, wherein The ratio of the divalent group represented by the formula (Y1-1) of Y1 is 10 to 50 mol% based on the entire structure of the formula (1) possessed by the polyimide precursor (a1), and the ratio of the divalent group represented by the formula (Y1-2) of Y1 is 10 to 50 mol% based on the entire structure of the formula (1) possessed by the polyimide precursor (a1).

3. The liquid crystal aligning agent according to claim 1 or 2, wherein: The polyimide precursor (a1) further includes a structure in which Y1 in the formula (1) is a divalent group represented by any of the following formulas (Y1-3) to (Y1-10) and (5-1) to (5-9), In the above formula, Boc represents the group shown below, 4. The liquid crystal aligning agent according to claim 1 or 2, wherein X1 in the formula (1) is at least one selected from the group consisting of structures represented by the following formulae (X1-1) to (X1-14), 5. The liquid crystal alignment agent according to claim 1, wherein The divalent group represented by the formula (Y1-1) is at least one selected from the group consisting of structures represented by the following formulae (D2-1) to (D2-5), In formulas (D2-1) to (D2-5), * represents a bonding bond, The divalent group represented by the formula (Y1-2) is at least one selected from the group consisting of structures represented by the following formulae (D4-1) to (D4-5), In formulas (D4-1) to (D4-5), * represents a bonding bond, X1 in the formula (1) is selected from the following (X1-3), 6. The liquid crystal aligning agent according to claim 1 or 2, wherein: The liquid crystal aligning agent further contains at least one polymer selected from the group consisting of polyamic acid, polyamic acid ester, polyimide, polysiloxane, polyester, cellulose derivatives, polyacetal, polystyrene derivatives, poly(styrene-maleimide) derivatives, and poly(meth)acrylate.

7. The liquid crystal alignment agent according to claim 6, wherein: The polymer is the following polymer (B), Polymer (B): at least one polymer selected from the group consisting of a polyimide precursor (b1) having a repeating unit represented by the following formula (2), and an imidized polymer (b2) of the polyimide precursor (b1), wherein the polyimide precursor (b1) comprises a structure in which Y2 in the following formula (2) is a divalent organic group having (i) a nitrogen atom bonded to an aromatic group or (ii) a nitrogen-containing aromatic heterocycle, In formula (2), X2 is a tetravalent organic group, Y2 is a divalent organic group, A3 and A4 are independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; in the molecular chain of the polyimide precursor (b1), X2, Y2, A3 and A4 are optionally present alone or in combination of two or more.

8. The liquid crystal alignment agent according to claim 7, wherein: In formula (2), the divalent organic group having (i) a nitrogen atom bonded to an aromatic group or (ii) a nitrogen-containing aromatic heterocycle is at least one selected from the following groups:

9. The liquid crystal alignment agent according to claim 1 or 2, wherein: The polymer (A) is a polymer whose main chain terminal is modified or capped.

10. The liquid crystal aligning agent according to claim 1 or 2, wherein The liquid crystal alignment agent further contains at least one additive selected from the group consisting of a dielectric, a conductive material, a silane coupling agent, a crosslinking compound, and an imidization accelerator. 11 . A liquid crystal alignment film obtained from the liquid crystal alignment agent according to claim 1 . 12 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 11 .

13. The liquid crystal display element according to claim 12, wherein: The liquid crystal display element is an IPS mode or FFS mode liquid crystal display element.

Citation Information

Patent Citations

  • Imide group-containing polyamic acid and its production as well as liquid crystal orienting agent

    JP1997185064A

  • Flight unit and control method of flight unit

    JP2019206332A

  • Material for liquid crystal alignment and liquid crystal displays made by using the same

    WO2004021076A1

  • Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display device

    CN110300922A

  • Liquid crystal alignment agent, liquid crystal alignment film and liquid crystal display element

    WO2018225811A1